AN ANALYTICAL STUDY ON THE INFLUENTIAL ROLE OF CHILDREN IN THE FAMILY BUYING DECISION - Bhargav, Sindura; Pujari, Dr. Bharati (The journal of contemporary issues in business and government, 2022)
Family buying decisions are significantly influenced by children. In the past, kids had much less market knowledge than their parents did. But now children are the first to learn about new things. Children today only watch as their parents make purchases. Children not only receive first choice of their own belongings but also of practically all other family members' belongings. The purpose of this study is to examine the influence of children on family shopping decisions utilising four distinct items. So this study looks into a range of variables that directly influence a family's purchasing choice. The study uses a descriptive research methodology using 153 samples. It has been collected from the respondents using a data collection method called a questionnaire. The data analysis method employed is the percentage method. The results demonstrate that most parents give importance to their children's requests because they think their child's choice is wise.